A dynamic state-space analysis of interpersonal emotion regulation in couples who smoke. (November 2014) - Butler, Emily A.; Hollenstein, Tom; Shoham, Varda; Rohrbaugh, Michael J.
Regulating emotions in interpersonal contexts requires managing one's own emotion, a partner's emotion, and the emotional tone of the relationship (e.g., conflict and intimacy). This multifaceted regulatory challenge, often referred to as "relationship-focused coping, " has been associated with health outcomes, but the real-time emotional processes involved are understudied. We use state-space grids (a recently developed graphical method) to investigate dynamic sequences of emotional experience (positive vs. negative) and relationship-focused coping intentions (to protect vs. engage one's partner) taken from 26 couples in which one or both partners were smokers, while they discussed a health-related disagreement during a nonsmoking baseline and then while smoking. State-space indicators of contingent emotion-coping sequences showed evidence of both successful regulation (associated with improving emotional state) and unsuccessful regulation (associated with worsening emotional state). The pattern of results suggests that interpersonal emotion regulation may interfere with smoking cessation differently depending upon whether one or both partners smoke.